(untitled) (Південний архів (історичні науки), 2023)
Purpose. The article aims to analyze the peculiarities of mentions of the accident at the Chornobyl nuclear power plant in all issues of the magazine ‘Perets’ in the period from 1986 to 1991. Methods. The content analysis method was applied to the collected dataset, employing both qualitative and quantitative approaches to study the documents. Results. Based on the results of the research, it was determined that the majority of the collected materials referencing the accident at the Chornobyl NPP consisted of journalistic opinion-based materials, while only a relatively small portion of the texts was written is satirical way. In the materials where the accident at the Chornobyl nuclear power plant was the main subject, that is, when the entire material was primarily dedicated to this event and its consequences, the study found the evidence of a profound transformation and weakening of USSR censorship. Initially, immediately after the accident, the «Perets» magazine published non-satiric journalistic materials that showed how spread anti-Soviet propaganda in Western media is, using the coverage of the accident as an example. However, later on, the magazine shifted towards publishing more opinion-based materials and satiric pieces that promoted anti-Soviet ideas. Publications where the accident at the Chornobyl nuclear power plant was only mentioned briefly revealed the complexity of social, political, environmental challenges, as well as the issue of national self-awareness reflected in the pages of the «Perets» magazine. The accident at the Chornobyl nuclear power plant became entangled with the whole set of problems peculiar to USSR in the late 1980s, including the inefficiency of state economic regulation, corruption in housing construction, non-payment of benefits to Chornobyl liquidators, and inequality in citizens’ access to public spaces etc. These opinionbased journalistic materials demonstrate that, on one hand, the accident at the Chornobyl nuclear power plant occurred when the social and economic situation in the USSR was already cconstrained, and on the other hand, the accident itself further intensified the existing tensions. These tendencies are even more evident in the satirical materials of the «Perets» materials where the accident at the Chornobyl nuclear power plant is mentioned only briefly. In such materials, the idea of preserving the environment is depicted as a national asset and is strongly emphasized. Simultaneously, environmental pollution, industrialization, and the possession of atomic technologies are portrayed as negative phenomena which is attributable to dictatorship. Conclusions. Therefore, the publications of the Perets magazine referring to the Chornobyl accident reflect two significant shifts: one in the work of the censorship apparatus within the structures of the late USSR, and the other in public opinion regarding the understanding of the causes and consequences of this disaster.